Serological survey of catteries for cats infected with feline coronavirus - Arshad, Siti Suri; Lee, W. W.; Hassan, Latiffah; Kamaruddin, A. I. M.; A. W., Siti Farawahida; Cheng, N. A. B. Y. (Veterinary Association Malaysia, 2005)
A serological survey on antibodies against feline coronavirus (FCo V) was conducted in four catteries in Klang Valley, Selangor, Malaysia. A total number of 24 cats of various breeds, ages and gender were randomly sampled from each cattery. The level of antibody titers were tested using a dot blot ELISA test kit ImmunofCombʳ, All cats showed a previous exposure to FeCo V. All the cats (100%) sampled from the catteries are infected with the virus. Approximately 42% and 58% of the sampled cats exhibited medium and high positive antibodies titers against FeCoY, respectively. This is the first study conducted in Malaysia to gauge the status of FeCo V antibody titer in cats.